2022
DOI: 10.3390/metabo12020109
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Metabolomics Reveal Acylcarnitines as Potential Biomarkers for Fatal Oxycodone-Related Intoxication

Abstract: Postmortem metabolomics has recently been suggested as a potential tool for discovering new biological markers able to assist in death investigations. Interpretation of oxycodone concentrations in postmortem cases is complicated, as oxycodone tolerance leads to overlapping concentrations for oxycodone intoxications versus non-intoxications. The primary aim of this study was to use postmortem metabolomics to identify potential endogenous biomarkers that discriminate between oxycodone-related intoxications and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
(46 reference statements)
1
11
0
1
Order By: Relevance
“…Postmortem metabolomics has been suggested as a tool in death investigation, with prior publications demonstrating the applicability in discriminating deaths attributable to pneumonia [5] and oxycodone intoxication [6]. These previous studies demonstrated the robustness of combining postmortem metabolomics and multivariate modeling, with validation testing resulting in sensitivity and specificity values between 80-86% and 76-84% [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postmortem metabolomics has been suggested as a tool in death investigation, with prior publications demonstrating the applicability in discriminating deaths attributable to pneumonia [5] and oxycodone intoxication [6]. These previous studies demonstrated the robustness of combining postmortem metabolomics and multivariate modeling, with validation testing resulting in sensitivity and specificity values between 80-86% and 76-84% [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, only a few studies have investigated the associations between metabolome differences and postmortem interval (PMI) [2][3][4]. However, advances have been made recently in expanding the utility of untargeted metabolomics as a potential tool in death investigations, specifically in deaths related to pneumonia [5] and oxycodone intoxication [6]. In these studies, untargeted metabolomics using multivariate statistical modeling could classify specific causes of death, with high sensitivity and specificity, based on the metabolic fingerprint of postmortem blood samples [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu biyokimyasal değişiklikler, oksikodon zehirlenmelerinde potansiyel bir biyobelirteç olarak açilkarnitinlerin kullanılabileceğini göstermiştir. 66 Son yıllarda adli toksikolojide ölüm ile cesedin bulunması arasındaki süre olan postmortem intervali (PMI) de araştırmak için de metabolom analizleri daha sık kullanılmaya başlanmıştır. Bu da adli toksikoloji alanında metabolomik yaklaşımların kullanıldığı diğer bir alandır.…”
Section: Maruziyet Biyobelirteçlerinin Ve Toksik Etki Mekanizmalarını...unclassified
“…The metabolomics methodology has emerged during the last 20 years and is yet in a relatively early phase of development but has so far proven valuable. Post mortem metabolomics could be a future analytical strategy used in post mortem toxicology (102,106).…”
Section: Metabolomicsmentioning
confidence: 99%